NOMINEE AGREEMENT REGARDING USE OF THE COASTAL AREA IN THE MENTAWAI ISLANDS - Ulya Atsani; Roni Efendi; Hidayati Fitri; Nurhikma .; Hebby Rahmatul Utamy (Masyarakat Indonesia, 2023)
Because of the multiple services that land serves, including maintaining a community's identity and an expanding economic function, land is an integral aspect of human life and existence. While land is the property of the state and is used in line with Article 33 Paragraph (1) of the Constitution of the Republic of Indonesia, it can be owned by private people or even communal property in the private sector. However, in the Mentawai Islands Regency, land managed by foreigners is given ownership status and is used through a nominee agreement process in both written and unwritten form. On the Mentawai Coast, nominee agreements are a type of land ownership and use through foreign investment, intermarriage and/or interfaith marriages, as well as through labor agreements, there is legal smuggling.Nominee, Use, Coastal Area